Learning path : Build apps for Amazon Web Services. - Morrow, Rich; Gallagher, Jon; Fowler, Kim; Suehring, Steve; Hand, Daniel; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Cloud computing is fast becoming the standard method of creating scalable, manageable web application services, and Amazon is leading the way. Master the complexities AWS and understand all of your options with this comprehensive Learning Path. Learn to make your existence in the cloud trouble-free."--Resource description page.
[Cloud computing with AWS / by Rich Morrow] -- Amazon Web Services : configure and manage your Amazon VPC / with Jon Gallagher -- Amazon Web Services, simple storage service / with Kim Fowler -- [Introduction to Amazon Web Services, EC2 deployment fundamentals / by Steve Suehring] -- Introduction to architecting for the cloud, Amazon AWS / with Daniel Hand.
Title and publication information from resource description page (Safari, viewed March 14, 2016).
Presenters, Rich Morrow, Jon Gallagher, Kim Fowler, Steve Suehring, Daniel Hand.
Keywords: Application software -- Development; Amazon Web Services; Cloud computing; Electronic books